Simbolismos, memórias e narrativas : redescobrindo a rua da Lama da década de 1980 - Gripp, Eduarda Cricco Miranda Barcelos (2016)
This research aimed to reveal symbolic aspects related to the past of a place in the city of Vitória/ES, Rua da Lama, from people who attended in the 1980s. This decade was chosen because it was the beginning of this emblematic region in the city, which